From stepping stone to the springboard: Alumni mobility, identity, and capital conversion in transnational higher education - Duffy, Liam; Li, Min (Journal of International Students, 2026)
This study examines alumni perspectives on the long-term impact of a Sino-U.S. joint-venture university. Qualitative interviews (n=13) and a supplementary survey (n=63) reveal that the institution functions as a strategic stepping stone to graduate education (88.9%) and fosters a global mindset. However, its effectiveness is moderated by persistent prestige deficits, inadequate career preparation (M=2.66/5), and underdeveloped alumni networks, reflecting tensions between American-modeled ideals and local realities. Applying Bourdieu’s framework of capital conversion, we find that PAU successfully facilitates cultural capital acquisition for graduate mobility but struggles with capital convertibility in domestic labor markets. As one of the first studies to center long-term alumni outcomes in Chinese transnational higher education, it offers critical insights for policymakers and practitioners navigating a post-pandemic landscape of constrained mobility and geopolitical uncertainty.